Enhancing Savonius Vertical Axis Wind Turbine Performance: A Comprehensive Approach with Numerical Analysis and Experimental Investigations - Al-Gburi K.A.H.; Alnaimi F.B.I.; Al-quraishi B.A.J.; Tan E.S.; Kareem A.K. (MDPI, 2024)
Small-scale vertical-axis wind power generation technologies such as Savonius wind turbines are gaining popularity in suburban and urban settings. Although vertical-axis wind turbines (VAWTs) may not be as efficient as their horizontal-axis counterparts, they often present better opportunities for integration within building structures. The main issue stems from the suboptimal aerodynamic design of Savonius turbine blades, resulting in lower efficiency and power output. To address this, modern turbine designs focus on optimizing various geometric aspects of the turbine to improve aerodynamic performance, efficiency, and overall effectiveness. This study developed a unique optimization method, incorporating a new blade geometry with guide gap flow for Savonius wind turbine blade design. The aerodynamic characteristics of the Savonius wind turbine blade were extensively analyzed using 3D ANSYS CFX software. The optimization process emphasized the power coefficient as the objective function while considering blade profiles, overlap ratio, and blade number as crucial design parameters. This objective was accomplished using the design of experiments (DOE) method with the Minitab statistical software. The research findings revealed that the novel turbine design OR0.109BS2BN2 outperformed the reference turbine with a 22.8% higher power coefficient. Furthermore, the results indicated a trade-off between the flow (swirling flow) through the gap guide flow and the impact blockage ratio, which resulted from the reduced channel width caused by the extended blade tip length. 2023 by the authors.